Dementia incidence among a cohort of lebanese older adults: first incidence estimates from the Middle East and North Africa region - Chaaya, Monique; Assaad, Sarah; Darwish, Hala; Haber, Marc; Khoury, Rosemary; Saab, Dahlia; El Asmar, Khalil; Hajjar, Ramzi (Frontiers in Dementia, 2025)
Objective To provide the first estimates of dementia incidence rates among elderly in Lebanon. Methods The cohort established in 2013 consisted of 470 elderly from Beirut and Mount Lebanon, who consented to be followed-up. In 2017, we reached 341 participants/informants, achieving a response rate of 72.6%. The validated Arabic version of the 10/66 Dementia Research Group diagnostic tool was administered through face-to-face interviews. Direct age standardization was applied to the data using the Western European population distribution. Age-, sex- and location-specific incidence rates were estimated. Results After 3.5 years of follow up, 19 new cases of dementia were identified among 229 surviving participants. The crude incidence rate was 16.8 per 1,000 p-y, and the age standardized rate was 20.5 per 1,000 p-y. The incidence rate increased with age, going from 6.5 for those aged 65–74 years to 54.0 for those aged 85–89 years. Incidence rate was higher among females than males (20.7 vs.12.0), and higher in Mount Lebanon, as compared to the capital city Beirut (19.5 vs.14.9). Conclusion Dementia incidence rate was close to European and North American countries' estimates. The use of validated tools increased the internal validity of our results. A large cohort study is warranted to confirm these results.